2022
DOI: 10.1038/s41557-022-01034-8
|View full text |Cite|
|
Sign up to set email alerts
|

Scalable and continuous access to pure cyclic polymers enabled by ‘quarantined’ heterogeneous catalysts

Abstract: Cyclic polymers are topologically interesting and envisioned as a lubricant material.However, scalable synthesis of pure cyclic polymers remains elusive. The most straightforward way is to recycle a used catalyst for the synthesis of cyclic polymers. Unfortunately, it is demanding because of the catalyst's vulnerability and inseparability from polymers, which depreciates the practicality of the process. Here, we develop a continuous process streamlined in a circular way that polymerization, polymer separation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 46 publications
0
20
0
Order By: Relevance
“…In the past decades a huge number of different techniques was developed for the synthesis of ring-shaped polymers covering a large variety of different monomers. Mainly two synthetic strategies were employed: the ring closure technique and the ring expansion technique (Figure ). In the ring closure approach, first linear precursors are synthesized using living or controlled polymerization techniques, which also allow for equipping the chain ends with functional groups.…”
Section: Synthesismentioning
confidence: 99%
“…In the past decades a huge number of different techniques was developed for the synthesis of ring-shaped polymers covering a large variety of different monomers. Mainly two synthetic strategies were employed: the ring closure technique and the ring expansion technique (Figure ). In the ring closure approach, first linear precursors are synthesized using living or controlled polymerization techniques, which also allow for equipping the chain ends with functional groups.…”
Section: Synthesismentioning
confidence: 99%
“…Recently, Grubbs et al reported the silica-supported ruthenium heterogeneous catalyst for the bulk REMP of cyclopentene, allowing catalyst recovery. 45 These catalysts have provided access to cyclic variants of commercially relevant and historically important polymers, such as poly(propylene), 14 poly(norbornene), 39−42 poly(methyl-1-pentene), 46 poly-(phenylacetylene), 47−49 and poly(acetylene). 50 Interestingly, upon doping, cyclic poly(acetylene) showed conductivity on the higher end of nonstretch aligned linear poly(acetylene), and cyclic poly(methyl-1-pentene) exhibited higher T g compared to its commercial linear counterpart while maintaining remarkable optical clarity.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Subsequent advances have led to homogeneous tantalum, tungsten, molybdenum, ruthenium, and vanadium , catalysts suitable for scalable cyclic polymer synthesis by REMP. Recently, Grubbs et al reported the silica-supported ruthenium heterogeneous catalyst for the bulk REMP of cyclopentene, allowing catalyst recovery . These catalysts have provided access to cyclic variants of commercially relevant and historically important polymers, such as poly­(propylene), poly­(norbornene), poly­(methyl-1-pentene), poly­(phenylacetylene), and poly­(acetylene) .…”
Section: Introductionmentioning
confidence: 99%
“…Tailored transition metal catalysts featuring a tethered metal–carbon multiple bond, or in one case a metallacyclobutane, are initiators for ring expansion metathesis polymerization (REMP). Cyclic alkenes, most commonly norbornene, , undergo ring expansion with tethered-metal carbon double bonds to give cyclic polymers. REMP of cyclic alkenes provides cyclic polymers with stereoregular chains, bottlebrushes, , gels, , and/or cross-linked networks .…”
Section: Introductionmentioning
confidence: 99%